Feminine Involvement in Violence: Differentiation between Myths and Realities: An Examination of Insurgency, Secession, Extremism, and Terrorism - Huda, Noor ul; Hanif, Sobia; Fida, Zeeshan (Journal of Development and Social Sciences, 2025)
This study looks at how to women are involved in revolt, separatist, extremist, and terrorist activities in an effort to distinguish between these beliefs and realities. Understanding women's motivations, involvement, and influence in various settings is the goal in order to debunk preconceptions and illuminate the complex realities. By dispelling widespread beliefs and preconceptions and illuminating the complicated realities of women's experiences in insurgency, separatist, extremist, and terrorist activities, this study aims to examine the intricacies of feminine involvement in violence.The involvement of women in violent movements calls into question long-standing assumptions and poses significant queries regarding gender, agency, and the nature of violence. The methodology used in this research is qualitative method and also used historical, descriptive, and analytical to understand the feminism involment . Women in violent movements have a variety of reasons and experiences, which should be acknowledged and addressed. It suggest to create are specific measures and regulations that take into consideration the complexity of women's role in violence. Encourage women to take part in peacebuilding and conflict resolution initiatives and to be empowered. Dispel popular misconceptions and preconceptions that support false beliefs about women's involvement in violent crimes.